High rates of sustained virological response despite premature discontinuation of directly acting antivirals in HCV‐infected patients treated in a real‐life setting. Issue 3 (2nd January 2021) - Fabbiani, Massimiliano; Lombardi, Andrea; Colaneri, Marta; Del Poggio, Paolo; Perini, Paolo; D'Ambrosio, Roberta; Degasperi, Elisabetta; Dibenedetto, Clara; Giorgini, Alessia; Pasulo, Luisa; Maggiolo, Franco; Castelli, Francesco; et al.
Abstract: In routine clinical practice, hepatitis C virus‐infected patients can prematurely discontinue the prescribed regimen for several reasons. The aim of our study was to investigate sustained virological response (SVR12) rates in patients who prematurely discontinued directly acting antiviral (DAA) regimens and to assess the shortest effective duration of DAA able to lead to SVR12. We retrospectively collected the SVR rates of patients, registered in the NAVIGATORE‐Lombardia Network database from January 2015, who discontinued DAAs before the predefined end of treatment. Overall, we included 365 patients, males were the majority (213, 58.4%), mean age was 60.5 years, and 53 (14.5%) patients were HIV‐co‐infected. Liver cirrhosis was observed in 251 (68.8%) subjects, and the most represented genotypes were 1b ( n = 168, 46%) and 3 ( n = 59, 16.2%). DAA was discontinued a median of 1 (IQR 1–4) weeks before the predefined EOT, with 164 (44.9%) patients stopping DAAs at least 2 weeks before the planned schedule. In patients with F0–F3 liver fibrosis, lower rates of SVR12 were observed in patients treated for <4 weeks: 50% ( n = 2/4) vs. 99.1% ( n = 109/110) for ≥4 weeks, p = 0.003. In patients with liver cirrhosis, lower rates of SVR12 were observed in patients treated <8 weeks: 83.3% ( n = 25/30) vs. 94.6% ( n = 209/221) for ≥8 weeks, p = 0.038. Despite premature discontinuation of DAA, high SVR12 rates were observed in a real‐life setting for treatment lasting at least 4 weeks in patients with liver fibrosis F0–F3 and 8 weeks in those with liver cirrhosis. On this basis, feasibility of reducing DAA treatment duration should be explored in randomized clinical trials.